2022
DOI: 10.21203/rs.3.rs-1779641/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

B cell class switch recombination is regulated by DYRK1A through MSH6 phosphorylation

Abstract: Protection from viral infections depends on immunoglobulin isotype switching, which endows antibodies with effector functions. Here, we found that the protein kinase DYRK1A is essential for B cell-mediated protection from viral infection and effective vaccination through regulation of class switch recombination (CSR). Dyrk1a-deficient B cells were impaired in CSR activity in vivo and in vitro. Phosphoproteomic screens and kinase-activity assays identified MSH6, a DNA mismatch repair protein, as a direct substr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…In this model, a Dyrk1a-mediated turnover of cyclin D3 served as a key mechanism for the proper transition from a proliferative state to quiescence. Furthermore, studies using mouse genetic models found that Dyrk1a plays an important role in mature B-cell function in response to infection or vaccination by regulation of class-switch recombination mediated by phosphorylation of mutS homolog 6 (MSH6) protein (Stoler-Barak et al, 2023). MSH6 is a part of a mismatch recognition complex that is mutated in several types of cancer, including the hereditary Lynch syndrome (Abildgaard et al, 2023).…”
Section: Dyrk1a In Cell Cycle and Cancermentioning
confidence: 99%
“…In this model, a Dyrk1a-mediated turnover of cyclin D3 served as a key mechanism for the proper transition from a proliferative state to quiescence. Furthermore, studies using mouse genetic models found that Dyrk1a plays an important role in mature B-cell function in response to infection or vaccination by regulation of class-switch recombination mediated by phosphorylation of mutS homolog 6 (MSH6) protein (Stoler-Barak et al, 2023). MSH6 is a part of a mismatch recognition complex that is mutated in several types of cancer, including the hereditary Lynch syndrome (Abildgaard et al, 2023).…”
Section: Dyrk1a In Cell Cycle and Cancermentioning
confidence: 99%